2023
DOI: 10.1111/nph.18859
|View full text |Cite
|
Sign up to set email alerts
|

Post‐secretory synthesis of a natural analog of iron‐gall ink in the black nectar of Melianthus spp.

Abstract: Summary The black nectar produced by Melianthus flowers is thought to serve as a visual attractant to bird pollinators, but the chemical identity and synthesis of the black pigment are unknown. A combination of analytical biochemistry, transcriptomics, proteomics, and enzyme assays was used to identify the pigment that gives Melianthus nectar its black color and how it is synthesized. Visual modeling of pollinators was also used to infer a potential function of the black coloration. High concentrations of el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…However, although progress has been made on identifying the genetic basis for variation of nectar volume (Galliot et al, 2006;Wessinger et al, 2014;Barstow et al, 2022) or sucrose as a percentage of total sugars (Prasifka et al, 2018), such knowledge is limited for the other nectar components. Enzymes and/or candidate genes (Roy et al, 2022;Magner et al, 2023) and a QTL (Kostyun The accumulation of DHA in nectar of m anuka and some other species of Leptospermum results in honey, which is highly valued both as a food and as a medicinal product. The economic importance of m anuka honey has resulted in it being not only one of the only woody perennial species for which nectary biology and nectar traits have been studied in detail but also one of the few species with green, photosynthetic nectaries to have been characterised.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, although progress has been made on identifying the genetic basis for variation of nectar volume (Galliot et al, 2006;Wessinger et al, 2014;Barstow et al, 2022) or sucrose as a percentage of total sugars (Prasifka et al, 2018), such knowledge is limited for the other nectar components. Enzymes and/or candidate genes (Roy et al, 2022;Magner et al, 2023) and a QTL (Kostyun The accumulation of DHA in nectar of m anuka and some other species of Leptospermum results in honey, which is highly valued both as a food and as a medicinal product. The economic importance of m anuka honey has resulted in it being not only one of the only woody perennial species for which nectary biology and nectar traits have been studied in detail but also one of the few species with green, photosynthetic nectaries to have been characterised.…”
Section: Discussionmentioning
confidence: 99%
“…However, although progress has been made on identifying the genetic basis for variation of nectar volume (Galliot et al ., 2006; Wessinger et al ., 2014; Barstow et al ., 2022) or sucrose as a percentage of total sugars (Prasifka et al ., 2018), such knowledge is limited for the other nectar components. Enzymes and/or candidate genes (Roy et al ., 2022; Magner et al ., 2023) and a QTL (Kostyun et al ., 2019) have been identified responsible for nectar colour in a few species, but data on the control of production of other metabolites are lacking, perhaps because of the potential difficulties in obtaining sufficient phenotypic and genomic data. In this study, by growing mānuka plants from across Aotearoa‐NZ in a common environment and combining nectar screening with genetic sequence analysis of a population segregating for nectar DHA content, facilitated by a new genome sequence assembly, we were able to identify QTLs associated with this notable nectar trait.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All eight species of Melianthus have been reported to produce darkcolored nectar, ranging from light gray to black, while their most closely related genus Bersama produces clear nectar (Henning, 2003). The evolutionary history of these lineages makes This article is a Commentary on Magner et al (2023), 239: 2026-2040. them a great system to study the evolution of specialized nectar traits and the implication of these traits in pollinator interaction and reproductive success. Future studies investigating the genetic variation of the iron-ellagate complex production pathways in these closely related species will shed further light on the evolution of black nectar.…”
Section: What Is the Evolutionary Origin Of The Black Nectar In Melia...mentioning
confidence: 99%
“…The latest to join the list of curious nectar compounds is the black pigment of Melianthus minor flowers. In an article published in this issue of New Phytologist, Magner et al (2023; 2026-2040 reported that ellagic acid, a heterotetracyclic compound that when complexed with ferric cations (Fe(III)), gives the nectar of M. minor flowers its characteristic black color. Coincidentally, this iron-ellagate complex is analogous to the iron-gallate and iron-tannate complexes that constitute the black pigment in iron-gall ink, the most common ink in use before the 20 th century (Fig.…”
mentioning
confidence: 99%